The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/or.2018.6575
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‑221 and miR‑222 in the cancer stroma is associated with malignant potential in colorectal cancer

Abstract: The cancer stroma is important in cancer development, however, whether the aberrant expression of microRNAs (miRNAs) in the cancer stroma is associated with cancer progression remains to be fully elucidated. The aim of the present study was to identify the miRNAs associated with liver metastasis in the cancer stroma of human colorectal cancer (CRC). Using laser capture microdissection, cancer stroma was obtained from the primary lesion of six patients with CRC with liver metastasis (CRCwLM) and six patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Then, the entire text of the remaining 362 studies was assessed, determining the removal of 312 further studies. Finally, 50 articles, published between 2009 and 2018, were included in the systematic review [35,36,37,38,39,40,41,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93]. A detailed flow-chart illustrating the literature selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the entire text of the remaining 362 studies was assessed, determining the removal of 312 further studies. Finally, 50 articles, published between 2009 and 2018, were included in the systematic review [35,36,37,38,39,40,41,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93]. A detailed flow-chart illustrating the literature selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The main general information on the included studies are reported in Table 1 and Table 2. Among them, 27 focused on miR-221 [36,38,40,52,54,57,60,61,62,64,69,70,72,73,74,75,79,80,81,82,83,84,85,88,89,91,92], 11 on miR-222 [37,39,53,56,59,63,67,68,86,87,93], and the remaining 12 investigated the cluster miR-221/miR-222 [35,41,51,55,58,65,66,71,76,77,78,90]. Overall, 6086 patients suffering from different tumors were included in the systematic review, with the sample size in each study ranging from 20 to 393 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In cells, miRNAs regulate a variety of important physiological and pathological processes, including cell proliferation (Han, Yin, & Zhang, ), differentiation (Wu et al, ), apoptosis (Yao, Pan, Du, Zhang, & Li, ), and hormone biosynthesis and secretion (Song et al, ). Previous studies have indicated that miR‐222 is an important regulatory factor for cancer development (Galardi et al, ; Gong et al, ; Gu et al, ; Guo et al, ; Huang, Ouyang, Wei, & Yu, ; Iida et al, ; le Sage et al, ; Liu et al, ). In the bovine ovaries, the expression level of miR‐222 was found to be low in preovulatory follicles and high in corpus luteum (Özdemir & Çomaklı, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although not as extensively studied as HDmiR‐122, CDmiR‐222 was shown to be abundantly expressed in biliary epithelium . Elevated levels have been reported in serum of patients with primary sclerosing cholangitis, in tissue of hepatocellular carcinoma and in primary colorectal cancer lesions with liver metastases . CDmiR‐222 was also found to be lower in the preservation solution of grafts that developed NAS after transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…HDmiR-122, but not CDmiR-222, at 30 min was associated with bicarbonate level in bile at 6 h NMP (D). Spearman's correlation coefficient (r) and P-value are indicated sclerosing cholangitis, in tissue of hepatocellular carcinoma and in primary colorectal cancer lesions with liver metastases [36][37][38]. CDmiR-222…”
mentioning
confidence: 99%